Remarkable High Thermoelectric Conversion Efficiency Materials of BeMF3 (M = Al, Y). Issue 11 (7th October 2020) - Sun, Hai‐Long; Yang, Chuan‐Lu; Wang, Mei‐Shan; Ma, Xiao‐Guang
Abstract: Large dimensionless figure of merit ( ZT ) and high thermoelectric conversion efficiency ( η ) are key factors to achieve practical application for the semiconductor materials. Here, two semiconductor materials of BeMF3 (M = Al, Y) with excellent thermoelectric performance are reported. In particular, the ZT and η of BeMF3 reach 4.76 and 48%, respectively, which are larger than those of all the reported thermoelectric materials in the literature. The electronic properties of BeMF3 with first‐principles calculations based on density functional theory are carried out. The geometrical structures of BeMF3 are fully relaxed and stabilities are confirmed by phonon dispersions. Transport properties are determined by the semiclassical Boltzmann transport theory with accurate band structures. The results show that the regions of the large Seebeck coefficients and electrical conductivity are overlapped with those of the small electronic thermal conductivity for the n‐ and p‐type systems and especially true for BeYF3, which brings about the enhanced ZT values. Moreover, the small lattice thermal conductivities also contribute to the large ZT values. Abstract : The excellent thermoelectric properties of BeMF3 (M = Al, Y) are identified. At a temperature of 1300 K, the n‐type BeYF3 can achieve a ZT maximum value of 4.76 and conversion efficiency of 48%, which are larger than all the reported values in the literature.